The Role of National Committees in Applying International Humanitarian Law - Iraq as a Model - Al-Gharawi, Fadel (Journal of Legal Sciences, 2022)
In many countries there are national committees for the implementation of international humanitarian law that aim to advise and assist their governments in implementing international humanitarian law and spreading knowledge about it. The responsibility for the formation of these committees rests with the states, supported by the International Committee of the Red Cross, as one of the ways to ensure the effective implementation of international humanitarian law. The national committees for international humanitarian law seek to urge governments to implement and ensure respect for international humanitarian law and to contribute to its enforcement and dissemination at the national level.